Banana Corm Crackers as a Sustainable Food Innovation for Community Nutrition and Local Economic Empowerment - Janruel P. Tupas; Sharmaine P. Leones; Cherry-ann E. Gumabay; Maureen V. Brillantes; Jay-anne L. Banglay; Rency P. Bacud (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
The utilization of banana corm for product diversification offers potential economic value, yet consumer preference remains a critical variable. This study aimed to determine the acceptability of Banana Corm Crackers in terms of three flavor variants (Lagundi, Pandan, and Turmeric), quality attributes (appearance, aroma, texture, and flavor), and packaging types (tub, transparent pastry box, and metallic stand-up pouch). Utilizing a descriptive-experimental research design, sensory evaluation was conducted with 30 Bachelor of Technical-Vocational Teacher Education (BTVTED) students majoring in Food and Service Management. Data were analyzed using Weighted Mean and Analysis of Variance (ANOVA). The results indicated that the Pandan flavor was the most preferred variant with a mean rating of 7.99 ("Like Very Much"), while the metallic stand-up pouch was identified as the most favorable packaging. Statistical analysis revealed significant differences in acceptability based on flavor and highly significant differences based on packaging; however, no significant differences were found regarding the general quality attributes across the variants. These findings imply that while the product quality is consistent, prioritizing the Pandan flavor and metallic packaging is crucial for maximizing market acceptability.